Efeito da imersão em própolis verde na estabilidade de cor e microdureza de resina composta: análise in vitro - Fabiana Costa Assis Magalhães (2024)
Effective management of oral complications related to radiotherapy is crucial, with a particular emphasis on the use of mouthwashes containing Brazilian green propolis. Composite resins, commonly used in dental restorations for these patients, may undergo changes in color and mechanical properties when exposed to these antiseptic solutions, whose effects are still unknown. This in vitro study aimed to evaluate the effect of immersing a composite resin (Filtek Z350 XT – 3M ESPE) in Brazilian green propolis extract solutions on color change and microhardness. Four shades of the resin were evaluated: A1B, A1E, CT, and A1D. Forty disc-shaped samples (2×10 mm) of each resin shade were randomly and equally divided into four groups according to the proposed solutions. Three groups were immersed in green propolis extract solutions: 11% aqueous extract (PAQ 11%), 11% alcoholic extract (PAL 11%), and 20% alcoholic extract (PAL 20%), while the control group was immersed in distilled water (H2O). The specimens were subjected to 6 hours of immersion. Color change was assessed using ultraviolet-visible reflection spectrophotometry with a spectrophotometer (CM-3700D, Konica Minolta). Microhardness (Vickers) was measured using a microhardness tester (Wilson VH1102, Buehler). Color differences (ΔE) were calculated using the CIELAB and CIEDE2000 systems. Color and microhardness were determined at the start and after immersion of the samples. Between readings, the samples were kept in a closed, dark place to simulate natural aging over 365 days. Data were analyzed using parametric and non-parametric analysis of variance, as well as multiple comparison tests (α=0.05). The ΔE values of all samples were not clinically acceptable. The ΔE values of the samples immersed in PAL 11% and 20% were not clinically acceptable for shades A1B and A1D. The solution and immersion period affected the resin's microhardness, except for water, which showed a decrease after 6 hours. The tested Brazilian green propolis extract solutions caused unacceptable color changes in the composite resin. Resins immersed in 20% alcoholic extract of green propolis exhibited significantly greater color changes to A1D shades. The microhardness values of the specimens in alcoholic solutions significantly increased in all colors after immersion.